PELATIHAN PEMBUKUAN SEDERHANA BAGI PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KELURAHAN LALODATI, KECAMATAN PUUWATU KOTA KENDARI - Alwi, La Ode; Nikoyan, Anas; Gafaruddin, Abdul; Kimon, La Ode (....-...., 2023)
The training of making simple accounting for UMKM perpetrators who are in the Lalodati district of Puuwatu City of Kendari aims to enhance the ability of UMKM actors in managing their business finances. The method used for the service activities of this society is by providing a training in the creation of accounting with the materials provided includes: the basics of the recording of transactions, the preparation of financial reports, the report of profit loss, balance sheet, and cash flow. Activities were carried out for 1 day at the Lalodati Kelurahan Office with 15 people involved. The results of these activities show that the majority of participants understand the importance of accounting to manage their business finances and are able to implement simple accounting for their business. As a result of the training, UMKM participants were able to show that the majority (70%) of training participants had known and was able to explain the importance of transaction recording in the enterprise, while 10 people (50%) had been able to carry out business transaction records and 5 people (25%) had continued with the preparation of financial reports. In addition, the participants have also tried to use the information from the financial report to make future business projections.